Analysis of car commuters knowledge, awareness and willing to modal shift in Klang Valley, Malaysia - Kaffashi, Sara; Shamsudin, Mad Nasir; Ahmad Sidique, Shaufique Fahmi; Bazrbachi, Abdullatif; Radam, Alias; Abdul Rahim, Khalid (Enviro Research Publishers, 2016)
The main objective of present study is to evaluate private vehicle commuters’ knowledge and concern about health and environmental impact of transportation related air pollution in Klang Valley, Malaysia. Data were collected using structured questionnaire and interviewing 450 car commuters in five main areas of Klang Valley. The Results indicated that majority of respondents (58%) have knowledge about deteriorating effect of transport on society’s health and welfare. While, only 36% of them were concern about the transport related environmental problems. This study suggest that government intervention through increasing toll, parking fee and introducing congestion fee together with providing more efficient public transport can reduce more than half of travels by car.